Compressive Strength of Three Types of Heat-Cure Acrylic Resins: Acropars, Acrosun, and Meliodent - A Neshati; N Kouchak Dezfouli; M Sadafi; Sh Omidi (Islamic Azad University, 2021)
Background: Compressive strength of acrylic resin base is an effective factor on durability of a prosthesis. The purpose of this in vitro study was to compare the compressive strength of three different types of heat-cure acrylic resins.  Materials and Methods: In this in vitro experimental study, 60 acrylic samples were fabricated from Acropars, Acrosun, and Meliodent acrylic resins (n=20 from each). The specimens were placed in a universal testing machine and force was applied until their fracture. The load at fracture was recorded as the compressive strength. Data were analyzed using one-way ANOVA followed by the Tukey's test.  Results: The mean compressive strength was 80.6 ± 6.9, 85.6 ± 6.9, and 71.9 ± 5.3 MPa for Acropars, Acrosun, and Meliodent, respectively. The compressive strength of Acrosun was significantly higher than that of other groups (P=0.047). Conclusion: In general, the results showed that the highest and the lowest compressive strength values were related to Acrosun and Meliodent, respectively. These results indicated the optimal compressive strength of Iranian acrylic resins.